Determinants of Default from Treatment among Tuberculosis Patients in Rachuonyo North Sub County, Homa-Bay County, Kenya - Mosiori, Kepha N. (JOOUST, 2021)
Poor adherence to treatment is a common occurrence and is associated with patients remaining infectious for longer periods, relapse, treatment failure and the emergence of multidrug resistant or extreme drug resistant tuberculosis (TB). This problem is further compounded by TB-Human immunodeficiency virus (HIV) co-infection putting a further burden on the drug burden that TB patients are taking. Moreover, there is a paucity of data on determinants of default from treatment among tuberculosis patients in western Kenya. The objective of this study was therefore to determine the determinants of default from treatment among TB patients in Rachuonyo North Sub County. This study used case-control study design utilizing both primary and secondary data to identify factors associated with treatment default using data from a cohort of patients adults registered during the period January (2011) and (Dec) 2014 in Rachuonyo North Sub-County Homabay County. The study enrolled a total of 297 of cases and controls (135 cases and 162 controls). Cases were a sample of registered TB patients receiving treatment under Direct Observed Treatment Short course [DOT(s)] that defaulted from treatment. Controls were those who began therapy and completed treatment. Secondary data was abstracted from TB register while primary data was collected using a standardized patient questionnaire. This study defined default as interrupting TB treatment for two or more consecutive visits during treatment and obtaining the final documented outcome as out of control (OOC/LTF). Bivariate logistic regression analysis was used to identify independent risk factors associated with default. The main reasons for defaulting included distance from health facility, relocation, stigma, longer time waiting and side effects of anti TB drugs, ignorance, drug shortage and feeling better. The risk factor for default included paying service charge (OR, 2.93; 95%CI 1.24-6.94), residing 6 Km from the health facility (OR, 5.06; 95%CI 2.05-12.49), staff having negative attitude (OR, 4.42; 95%CI 2.07-9.42), perception that staff in health facility were not skilled (OR, 2.97; 95%CI 1.52-5.77), health facility not well equipped (OR, 2.76; 95%CI 1.36-5.59), lack patient Support Structure (OR, 3.05; 95%CI 1.62-5.75) and lack of patient recognition (OR, 13.36; 95%CI 4.47- 39.98).. Further analysis revealed that those who had not disclosed their TB status (OR, 2.90; 95%CI 1.27-6.60), those who were not getting household support (OR, 1.11; 95%CI 0.67-1.83) and those taking drugs and substances (OR, 2.37; 95%CI 1.37-4.20) were more likely to default from TB treatment. In conclusion, multiple factors including distance, staff having negative attitude, lack of patient support structure and recognition were independently associated with default. There is a need for integrated interventions that addressed patient and health facility related factors that lead to TB treatment default among patients.
Keywords: Direct Observational Treatment Short Course (DOTs); Extensively Drug-Resistant Tuberculosis (XDR-TB)